The influence of offside rule and pitch sizes on the youth soccer players` small-sided games external loads - Castillo, D.; Raya-González, J.; Clemente, F. M.; Yanci, J. (Research in Sports Medicine, 2020)
The aim was to analyse the influence of the offside rule and pitch sizes on the external loads encountered by young soccer players during small-sided games (SSGs). Twenty-four U12 soccer players belonged to the same Spanish Performance Soccer Academy participated in the study. Each player participated in six different SSGs attending to the offside rule (i.e., offside not applicable [NOS] and with offside [WOS]) and the pitch sizes (i.e., individual interaction space [IIS] of 25, 50 and 75 m2 per player). The obtained data included measures of external loads by global positioning systems. Players covered higher total distance and greater distances at jogging (8-12.9 km·h-1), cruising (13.0-16.0 km·h-1) and sprinting (>16.0 km·h-1) in NOS75 and WOS75 SSGs (p <0.01; d =0.65-6.60). Besides, in the NOS75 SSG, the total distance and the distance at cruising were higher in respect to WOS75 (p <0.01; d =0.63-0.82). In addition, players performed lower sprints (p <0.01; d =1.17-1.71) and achieved lower Vmax (p >0.05; d =1.10-1.88) during NOS25 and WOS25 SSGs. These findings could provide relevant information for coaches in order to apply different pitch sizes and the inclusion/absence of the offside rule throughout the microcycle.